Comparative anatomy of the carotid canal in the Miocene small-bodied catarrhine Pliobates cataloniae. Issue 161 (December 2021) - Bouchet, Florian; Urciuoli, Alessandro; Beaudet, Amélie; Pina, Marta; Moyà-Solà, Salvador; Alba, David M.
Abstract: The small-bodied Miocene catarrhine Pliobates cataloniae (11.6 Ma, Spain) displays a mosaic of catarrhine symplesiomorphies and hominoid synapomorphies that hinders deciphering its phylogenetic relationships. Based on cladistic analyses, it has been interpreted as a stem hominoid or as a pliopithecoid. Intriguingly, the carotid canal orientation of Pliobates was originally described as hylobatid-like. The variation in carotid canal morphology among anthropoid clades shown in previous studies suggests that this structure might be phylogenetically informative. However, its potential for phylogenetic reconstruction among extinct catarrhines remains largely unexplored. Here we quantify the orientation, proportions, and course of the carotid canal in Pliobates, extant anthropoids and other Miocene catarrhines ( Epipliopithecus, Victoriapithecus, and Ekembo ) using three-dimensional morphometric techniques. We also compute phylogenetic signal and reconstruct the ancestral carotid canal course for main anthropoid clades. Our results reveal that carotid canal morphology embeds strong phylogenetic signal but mostly discriminates between platyrrhines and catarrhines, with an extensive overlap among extant catarrhine families. The analyzed extinct taxa display a quite similar carotid canal morphology more closely resembling that of extant catarrhines. Nevertheless, our results for Pliobates highlight some differences compared with the pliopithecid Epipliopithecus, which displays a somewhat more platyrrhine-like morphology. In contrast, Pliobates appears as derived toward the modern catarrhine condition as the stem cercopithecid Victoriapithecus and the stem hominoid Ekembo, which more closely resemble one another. Moreover, Pliobates appears somewhat derived toward the reconstructed ancestral hominoid morphotype, being more similar than other Miocene catarrhines to the condition of great apes and the hylobatid Symphalangus . Overall, our results rule out previously noted similarities in carotid canal morphology between Pliobates and hylobatids, but do not show particular similarities with pliopithecoids either—as opposed to extant and other extinct catarrhines. Additional analyses will be required to clarify the phylogenetic relationships of Pliobates, particularly given its dental similarities with dendropithecids.